DOI: 10.24834/isbn.9789178773251
|View full text |Cite
|
Sign up to set email alerts
|

Connecting sialic acid expression to cancer cell characteristics: Novel tools for detection, imaging, and analysis

Abstract: Sialic acid (SA) plays a crucial role in many biological processes. Cell surface SA expression is usually analyzed with antibodies or lectins; however, they are costly and with poor stability. We have used a molecular imprinting technique to synthesize an alternative SA receptor – SA molecularly imprinted polymers(SA-MIPs) with an embedded fluorophore for fluorescent detection of theSA-MIPs. The binding behavior and specificity of SA-MIPs were verified by using lectins and SA conjugates on cancer cell lines, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 135 publications
(182 reference statements)
0
1
0
Order By: Relevance
“…The comparable size of AuNPs to enzymes, combined with their unique physicochemical properties, facilitates efficient electronic coupling processes. Studies in this area have shown that gold nanoparticles not only serve as the enzyme carriers but also actively participate in aligning enzymes on their surfaces and directly wiring the redox center to the electrode [90][91][92][93][94]. Some theories explain this through the large surface area-to-volume ratio of gold nanoparticles.…”
Section: Enzymes On Gold Nanoparticles (Aunps) Modified Electrodesmentioning
confidence: 99%
“…The comparable size of AuNPs to enzymes, combined with their unique physicochemical properties, facilitates efficient electronic coupling processes. Studies in this area have shown that gold nanoparticles not only serve as the enzyme carriers but also actively participate in aligning enzymes on their surfaces and directly wiring the redox center to the electrode [90][91][92][93][94]. Some theories explain this through the large surface area-to-volume ratio of gold nanoparticles.…”
Section: Enzymes On Gold Nanoparticles (Aunps) Modified Electrodesmentioning
confidence: 99%